Breaking long-range order in iridium oxide by alkali ion for efficient water oxidation - Gao, Jiajian (2020)
Oxygen electrochemistry plays a critical role in clean energy technologies such as fuel cells and electrolyzers, but the oxygen evolution reaction (OER) severely restricts the efficiency of these devices due to its slow kinetics. Here, we show that via incorporation of lithium ion into iridium oxide, the thus obtained amorphous iridium oxide (Li–IrOx) demonstrates outstanding water oxidation activity with an OER current density of 10 mA/cm2 at 270 mV overpotential for 10 h of continuous operation in acidic electrolyte. DFT calculations show that lithium incorporation into iridium oxide is able to lower the activation barrier for OER. X-ray absorption characterizations indicate that both amorphous Li–IrOx and rutile IrO2 own similar [IrO6] octahedron units but have different [IrO6] octahedron connection modes. Oxidation of iridium to higher oxidation states along with shrinkage in the Ir–O bond was observed by in situ X-ray absorption spectroscopy on amorphous Li–IrOx, but not on rutile IrO2 under OER operando conditions. The much more “flexible” disordered [IrO6] octahedrons with higher oxidation states in amorphous Li–IrOx as compared to the periodically interconnected “rigid” [IrO6] octahedrons in crystalline IrO2 are able to act as more electrophilic centers and thus effectively promote the fast turnover of water oxidation.